Answer is linked below.
![Answer is linked below class=](https://us-static.z-dn.net/files/d7c/3647ee05e00b8c145761a2a264312ea5.png)
Answer:
Step-by-step explanation:
Given:
Find B + C - A:
A = [tex]3x² - 7x + 8[/tex]
B = [tex]x² + 8x - 3[/tex]
C = [tex]-5x²-3x + 2[/tex]
Lets find B + C - A :
→ [tex]B + C - A[/tex]
→ [tex]x² + 8x - 3+ (- 5x²-3x + 2)-(3x² - 7x + 8)[/tex]
→ [tex]x² + 8x - 3-5x² - 3x + 2-3x² + 7x - 8[/tex]
→[tex] (1-5-3)x² + (8 -3 + 7)x+ (-3 + 2 - 8)[/tex]
→ [tex]- 7x² + 12x - 9[/tex]